Development of a safer laboratory vervet monkey model for the study of human African trypanosomiasis - Maxwell Waema; Naomi Maina; Simon Karanja; Beatrice Gachie; Maina Ngotho; John Kagira (AOSIS, 2014)
Background: There are three subspecies of Trypanosoma brucei: T. b. gambiense, T. b. rhodesiense and T. b. brucei. The first two are infectious to humans, whilst T. b. brucei is not. Identifying an animal model of T. b. brucei that mimics human African trypanosomiasis (HAT) would enable researchers to study HAT without subjecting themselves to undue risks such as accidental infection. Objectives: This study assessed the sequential clinical, parasitological and haematological changes in vervet monkeys infected with T. b. brucei. Methods: Three vervet monkeys were infected with a 104 inoculum of T. b. brucei (isolate GUTat 1). Late-stage disease was induced by subcurative treatment with diminazene aceturate 28 days post-infection. The animals were treated curatively with melarsoprol upon relapse. Parasitaemia and clinical signs were monitored daily and, at weekly intervals, the monkeys' blood and cerebrospinal fluid (CSF) were sampled for haematology and parasitosis assessments, respectively. Results: The first-peak parasitaemia was observed between seven and nine days post-infection. Clinical signs associated with the disease included fever, dullness, pallor of mucous membranes, lymphadenopathy, splenomegaly and oedema. Late-stage signs included stiffness of joints and lethargy. The monkeys developed a disease associated with microcytic hypochromic anaemia. There was an initial decline, followed by an increase, in total white blood cell counts from early- to late-stage disease. Trypanosomes were detected in the CSF and there was a significant increase in white cell counts in the CSF during late-stage disease. Infected vervet monkeys displayed classical clinical symptoms, parasitological and haematological trends that were similar to monkeys infected withT.b. rhodesiense. Conclusion: The T. b. brucei vervet monkey model can be used for studying HAT without putting laboratory technicians and researchers at high risk of accidental infection.